Tick fever agents in dairy cattle from a tropical region subjected to different breeding systems: Parasitological, clinical, serological aspects and genetic diversity of Anaplasma marginale - Cavalcante, Alliny Souza de Assis; Ribeiro, Nathalia Braz; Paula, Warley Vieira de Freitas; Sales, Kamila Gaudêncio da Silva; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Calchi, Ana Claudia [UNESP]; Krawczak, Felipe da Silva; Ferreira, Lorena Lopes; Bastos, Camila Valgas; Dantas-Torres, Filipe; Soares, Vando Edésio; et al. (Elsevier, 2025)
This study aimed to evaluate the infection dynamics by TF agents in heifers from birth to first calving, in contact with R. microplus, correlating parasitological, serological and clinical aspects of the infection. We also evaluate the persistence of the infection by TF agents in cows raised with or without contact with R. microplus, and the genetic diversity of A. marginale. Three studies were performed. In the first, 15 Girolando heifers (15/16 Holstein × 1/16 Gyr) were used and monitored from birth until their first calving (start of lactation), totaling 28 months of monitoring. In study 2, cows between the 1st and 6th lactation, which were raised on Compost Barn during lactation and on pasture during the dry period, were evaluated. In study 3, cows from the 1st to 7th lactation that after the first calving had no more contact with the cattle tick were evaluated. The animals were evaluated for parasitological, clinical, serological aspects and genetic diversity of Anaplasma marginale. Calves raised on pasture in contact with R. microplus in a tropical region reached a TF agent positivity ≥75 % at 4 months of age. TF cases occurred mostly after weaning, between 3 and 8 months of age. There was a correlation in A. marginale bacteremia between qPCR and blood smear, but no correlation between bacteremia and iELISA. Calves exposed to ticks between 3 and 8 months of age tended not to develop clinical TF as adults, even when continually exposed to R. microplus. Serologic or molecular results for B. bovis and B. bigemina in cows should be interpreted with caution, as the presence of these agents in less than 75 % of the herd may not indicate enzootic instability. In addition, cows exposed to ticks during dry-off had infections with higher levels of A. marginale in the 5th and 6th lactations. On the other hand, cows that had no further contact with R. microplus after their first calving showed infections with higher A. marginale levels in the first lactation. The A. marginale msp4 genotypes reported herein are the ones previously reported in Brazil.